Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction